Nepali Version of Geriatric Depression Scale-15 – A Reliability and Validation Study - Risal, Ajay; Giri, Eliza; Shrestha, Oshin; Manandhar, Sabina; Kunwar, Dipak; Amatya, Richa; Manandhar, Nirmala; Manandhar, Kedar; Holen, Are (Journal of Nepal Health Research Council, 2020)
Background: Geriatric depression is a significant problem in both the developed and the developing world. To identify this condition, Geriatric Depression Scale has been used in different languages and cultural settings; it has proved to be a reliable and valid instrument. However, the Geriatric Depression Scale-15 version in Nepali has so far not been validated.Methods: The original 15-item version of the Geriatric Depression Scale-15 was translated into Nepali and administered by trained nurses to a target sample aged ?60 years at Dhulikhel Hospital (n=106). Subsequently, the participants were blindly interviewed by a consultant psychiatrist for possible geriatric depression according to the ICD-10 criteria. Cronbach’s alpha checked the reliability. Validity was assessed for three different cut-off points (4/5, 5/6, and 6/7); the related sensitivity, specificity, positive predictive value, and the negative predictive value of the scale were estimated.Results: The mean participant age was 68.1 (±7.2); males and females, 50.9% and 49.1%, respectively. Cronbach’s alpha was 0.79.The optimal cut-off point was found to be 5/6 with sensitivity and specificity 86.3% and 74.5%, respectively. Conclusions: Using a standard statistical protocol, a reliable and valid Geriatric Depression Scale-15-Nepali was developed with an adequate internal consistency and an optimal balance between sensitivity and specificity at cut-off point 5/6.The Geriatric Depression Scale-15-Nepali can serve as an appropriate instrument for assessing geriatric depression in epidemiological research as well as in primary health care settings in Nepal.Keywords: Geriatric depression; internal consistency; sensitivity; South Asia; specificity.